INITIAL TEACHER TRAINING FOR THE CULTURAL DIVERSITY INCLUSION - Figueredo Canosa, Victoria (2017)
This research is focused on the description and analysis of the initial training received by primary education teachers in Andalusia in connection with work in culturally diverse contexts. To this end, a qualitative method design with a descriptive and interpretive approach was chosen, using documental and content analysis as a research technique. This allows the identification and study of references to cultural diversity, explicit and implicit, present in the different dimensions of analysis: objectives, competencies, contents, learning outcomes, formative strategies and evaluation systems. The results indicate that, although all the curricular designs examined include references to cultural diversity, these references are scarce. Additionally, planning and coordination in relation to the intercultural competencies acquisition process is not observed, nor their crosswise treatment along the curriculum.